Magnetoelectric Catalysis: Magnetoelectrically Driven Catalytic Degradation of Organics (Adv. Mater. 28/2019). Issue 28 (10th July 2019) - Mushtaq, Fajer; Chen, Xiangzhong; Torlakcik, Harun; Steuer, Christian; Hoop, Marcus; Siringil, Erdem Can; Marti, Xavi; Limburg, Gregory; Stipp, Patrick; Nelson, Bradley J.; Pané, Salvador
Abstract : Nanocatalysts that deliver enhanced water remediation while using clean energy sources present a strong potential for solving many environmental challenges. In article number1901378, Fajer Mushtaq, Xiangzhong Chen, Salvador Pané, and co‐workers present core–shell magnetoelectric cobalt ferrite@bismuth ferrite nanoparticles that degrade over 85% of pharmaceuticals and industrial pigments under alternating magnetic fields by generating transient changes in their polarization state.